Cognition and behavior in adults with neurofibromatosis type 1 - Bos-Roubos, Anja; van Leeuwen, Hanneke; Wingbermühle, Ellen; van den Bosch, Louisa; Ossewaarde, Lindsey; Taal, Walter; de Graaff, Laura; Egger, Jos (Frontiers in Neurology, 2024)
BackgroundNeurofibromatosis Type 1 (NF1) is a congenital neurocutaneous disorder. As NF1 is incurable and presents with a wide range of physical and mental symptoms, knowledge of neurocognitive and behavioral functioning can be an important aid in understanding their functional impact, and developing treatment options. To date, studies in children with NF1 have shown dysfunction in several domains, but much less is known about cognition and behavior in adults with NF1. The present study describes the neuropsychological phenotype of adults with NF1 based on comprehensive clinical examination of cognition and behavior across multiple functions.MethodsParticipants were 62 adults with NF1 (mean age 38.2 years; SD 13.4). All underwent individual clinical neuropsychological assessment at the Center of Excellence for Neuropsychiatry as part of regular care. Scores on all individual measures were standardized into z-scores based on the corresponding normative group data. The proportions of mean z-scores in the NF1 study group were calculated according to cut-off points (±1 to ±1.5 SD; > ±1.5 SD) and compared to the expected proportions in the normal population distribution. Cognition and behavior was tested against population means constructed by bootstrapping.ResultsPerformance on the cognitive measures oral reading speed, visuospatial copying, visuospatial immediate recall, visual learning/imprinting, and visual memory immediate recall in the NF1 group were lower than normative means. The behavioral measures indicated higher levels of dysfunction, including psychopathology. The proportions of the NF1 study group with lower cognitive performance and higher levels of behavioral dysfunction were larger than in the normal population distributions. In addition, domain-level results revealed that intelligence, attention/speed, memory, and social cognition reflect cognitive dysfunction. Moreover, levels of emotion perception problems, experienced executive dysfunction, internalizing psychopathology (e.g., anxiety, depression), and severe fatigue were significantly higher compared to the simulated population sample. The mean level of emotion regulation (coping strategies) did not differ significantly from the population.ConclusionIdentified cognitive and behavioral dysfunction in multiple domains indicates high vulnerability in adults with NF1 and underscores the importance of individualized neuropsychological assessment and treatment. Further research on the relationships between cognition and behavior (including fatigue) in NF1 is warranted.